Unexpected events attributed to vaccination or immunization (ESAVI) reported to the COVID-19 vaccine at the National Maternal Perinatal Institute - Chipa Avila, Mishel Rocio (2022)
Objective. To describe the ESAVIs reported in the immunization carried out on health personnel with the Sinopharm vaccine (Vero cell) and to verify the causality of suspected adverse reactions. Material and methods. The study has a quantitative approach and cross-sectional design. It was developed at the National Maternal Perinatal Institute in 2021, where 60 workers who manifested some type of reaction after immunization (first and second dose) were evaluated. The instruments used were the ESAVI report sheet and the instructions for the decision algorithm for the evaluation of causality of an ADR, Karch and Lasagna, proposed by the Peruvian Pharmacovigilance System of the DIGEMID. Results. It was verified that the highest percentage of ESAVI reports occurred in the female sex, between the ages of 30 to 59 years. The most reported clinical manifestations were headache, diarrhea, dizziness and weakness. It was shown that the categories assigned as "probable", with 84.8%, and "definite", with 15.2%, were the total reported. In addition, in the mild ESAVI, 75.8% were in the "probable" category and only in the first dose was a severe case of ESAVI reported. Conclusions. The most frequent reports occurred in the female sex and the ESAVI, defined with the category of "probable" causality, were the most reported.